SPATIAL MAPPING AND ASSESSMENT OF SOIL ERODIBILITY USING GIS IN THE MIDDLE OF ERBIL PROVINCE - D. R. Keya; H. O. Salih; A.E. P. Hayder; A. O. Mawlood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to estimate soil erodibility in the middle of Erbil province. The results of indirect methods were compared with the observed K-factor in order to determine the most suitable method. The tests were carried out for nine soil locations by taking samples from topsoil. Samples were analyzed for physicochemical properties. The soil in study area is mostly clay and silt clay. The analysis was performed using three assessment models of soil erodibility; the Erosion Productivity Impact Calculator (EPIC), Vaezi et al and Universal Soil Loss Equation (USLE) models. Soil erodibility for direct measured K values varied from 0.27 to 0.39 t h MJ−1mm−1 with standard deviation of 0.041 t h MJ−1mm−1. The statistical evaluation of the models for K-factor estimation showed that the EPIC and USLE nomograph models were the most suitable models for the studied area.